SIMULTANEOUS PRODUCTION OF VIRGIN COCONUT OIL AND COCONUT PROTEIN ISOLATE IN FOOD APPLICATION - Xaveria, Audrey
One of coconut oil products that has the potential to be developed and has high economic value is Virgin Coconut Oil (VCO), but the production of VCO generate wastes that still can be used, which one of them is blondo. This study aims to determine the effect of coconut milk extraction temperature and pH on VCO and protein isolate production by full factorial experimental design with center point. The experiment was carried out in 25 and 45oC for extraction temperature, 5 and 9 for extraction pH, with center point in 35oC dan pH of 7. The recovery of VCO from this experiment were within the range of 12- 41% (g VCO/g oil in coconut). Meanwhile the recovery of protein isolate was within the range of 2-5% (g protein/g protein in coconut). Based on this experiment, pH of coconut milk extraction significantly affects the recovery of VCO and protein in coconut milk, but not significantly affects the recovery of protein isolate. The increase of pH in coconut milk extraction, increase the recovery of VCO and protein in coconut milk. The temperature of coconut milk extraction did not significantly affect the recovery of coconut protein isolate and VCO obtained. The increase of temperature in coconut milk extraction, decrease the recovery of coconut protein isolate. The highest VCO and protein isolate recovery was obtained from coconut milk extracted at 35oC and pH of 7, with recovery of VCO and protein isolate were 40,56% and 8,04%. This variation was produced in large scale for quality analysis. From the analysis, acid value and saponification value obtained were higher than SNI maximum value, and the results were 0,23 and 262,92. Moisture content of the VCO was 0,37%, which still within the range of SNI. Emulsification activity index (EAI) and emulsification stability index (ESI) of coconut protein isolate were 174,53 m2/g and 20,14 minutes, which were lower than soy protein isolate. Meanwhile, foam capacity (FC) and foam stability (FS) of coconut protein isolate were higher than soy protein isolate, with FC and FS values of 54% and 61,68% respectively. Protein content of coconut protein isolate was 37,29%.